Social networking service messages improve novice trainees' motivation and performance of skills - Yamane, Yusuke; Arai, Junichi; Shinohara, Shota; Ozeki, Keisuke; Ishii, Minori; Matsumoto, Keitaro; Nagayasu, Takeshi (Asian journal of endoscopic surgery, 2024)
Purpose We examined the usefulness of positive social networking service (SNS) messages to improve motivation and performance during off‐the‐job training. Methods Subjects were sixth‐year medical students who completed a 4‐week clinical clerkship in our department involving two separate tasks. Time taken to perform the tasks was recorded on Days 1, 14, and 28. All trainees voluntarily practiced the task until Day 14. The trainees were classified into two groups according to the results of their time measurements on Day 14. The slow time group was intervened with SNS messages (SNS group) and the fast time group was not intervened (non SNS group, nSNS). The SNS group received messages from the moderator daily or every other day. The time to complete the skills practiced in the first (Days 1–14) and second half (Days 15–28) were recorded for each group. Results On Day 14, the time for both tasks of the nSNS group was significantly faster than the SNS group. However, there was no significant time difference on Day 28. During Days 15–28, the SNS group had significantly more practice days than the nSNS group (5.3 vs. 3.8 days, p = .023). On questionnaire, all SNS group participants indicated that the messages increased their motivation to practice. Conclusions SNS messages using smartphones might have increased motivation for task training and improved the performance of tasks in off‐the‐job training for novice trainees.